2011
DOI: 10.2174/092986711793979715
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genetic Variability in Nicotinic Acetylcholine Receptors on Nicotine Addiction and Smoking Cessation Treatment

Abstract: Nicotine dependence (ND) is one of the world's leading causes of preventable death. Nicotine addiction and other forms of drug addiction continue to be significant public health problems in the world. Evidence for a genetic influence on smoking behaviour and ND has prompted a search for susceptibility genes. Evidence has recently accumulated that single nucleotide polymorphisms (SNPs) in the genetic region encoding the nicotinic acetylcholine receptor (nAChR) subunits α6, α5, α3, and β4 are associated with smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 0 publications
0
19
0
2
Order By: Relevance
“…Moreover, we postulate that HR animals display augmentation of reward-related dopamine signaling (Flagel et al,2011) through differences in nAChR function in both the cell body (Fagen et al,2007) and terminal regions (current study) of the mesolimbic dopamine system. Indeed, smoking cessation treatments that target nAChRs have been shown to engender wide individual variability in treatment outcomes (Russo et al,2011). These data may inform personalization of pharmacotherapeutic interventions, perhaps based on measures of sensation seeking, and could also lead to novel therapeutic approaches to learning deficits in other neuropsychiatric disorders.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Moreover, we postulate that HR animals display augmentation of reward-related dopamine signaling (Flagel et al,2011) through differences in nAChR function in both the cell body (Fagen et al,2007) and terminal regions (current study) of the mesolimbic dopamine system. Indeed, smoking cessation treatments that target nAChRs have been shown to engender wide individual variability in treatment outcomes (Russo et al,2011). These data may inform personalization of pharmacotherapeutic interventions, perhaps based on measures of sensation seeking, and could also lead to novel therapeutic approaches to learning deficits in other neuropsychiatric disorders.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Drug discrimination assays have been used in attempts to isolate the receptor that is most relevant to nicotine's interoceptive effects, and several lines of evidence indicate that these are also mediated through the ␣4␤2 subtype of the nAChR (for review, see Smith and Stolerman, 2009). Nevertheless, genetic studies in particular have implicated other nicotinic receptor subtypes, such as the ␣3, ␣5, ␣6, and ␤4 subunits, in the abuse liability of nicotine (Improgo et al, 2010;Sherva et al, 2010;Russo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The observed interaction effect helps to reveal that not all individuals who were high in ADHD symptoms also reported problems with smoking. Researchers have suggested that certain aspects of neurocognitive functioning, such as sustained attention (Greenbaum & Lerer, 2009; Rigbi et al, 2008; Russo et al, 2011; Ware et al, 2011; Winterer et al, 2010; Zhang et al, 2010), could be a potential mechanism for both smoking vulnerability and components of the ADHD phenotype. Also, variation in subunits of the nAChRs, including rs13280604, plays a role in dopamine modulation which may affect ADHD symptoms and reinforce cigarette usage (Zeiger et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Variants of nicotinic-acetylcholine receptor (nAChR) complex genes have been widely studied as predictors of a range of smoking outcomes (Greenbaum & Lerer, 2009; Russo et al, 2011; Ware, van den Bree, & Munafo, 2011; Winterer et al, 2010; Zhang, Kranzler, Poling, & Gelernter, 2010). Eleven different nAChR subunit-encoding genes have been identified, including the CHRNB3 and CHRNA6 genes, both of which are located at chromosome 8p11.2.…”
Section: Introductionmentioning
confidence: 99%